Methanogenic bacteria as endosymbionts of the ciliate Nyctotherus ovalis in the cockroach hindgut. - Gijzen, H J (1991)
Production of methane in the hindgut of the cockroach Periplaneta americana was found to vary, depending on the feeding regimen. Methane production was positively correlated with the numbers of the ciliate Nyctotherus ovalis living in the cockroach hindgut. Defaunation of the cockroaches by means of low concentrations of metronidazole (Flagyl) resulted in a quick drop of methane production. Addition of the methanogenic substrates acetate and formate to isolated hindguts stimulated methane production. Inside the ciliate cells, autofluorescing bacteria could be demonstrated which were presumed to be methanogens. Electron microscopy revealed that the bacteria resembled Methanobrevibacter and that they were closely associated with organelles which contained infolded membranes and which were presumably hydrogenosomes.